2018
DOI: 10.1155/2018/6374374
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plasma Albumin on the Pharmacokinetics of Esomeprazole in ICU Patients

Abstract: Objectives To evaluate the effects of plasma albumin on pharmacokinetics of esomeprazole in ICU patients. Methods This study was performed in 32 consecutive intensive care unit (ICU) patients. They were divided into two groups according to the plasma albumin levels. Nineteen patients with low plasma albumin levels (<30 g/L; male/female, 12/7) were assigned to low plasma albumin group (LPAG). Thirteen patients with plasma albumin levels >30 g/L (male/female, 9/4) were assigned to high plasma albumin group (HPAG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
(26 reference statements)
1
7
0
5
Order By: Relevance
“…The mean t 1/2 of esomeprazole in this study (3.29 h) was much higher than that reported in healthy volunteers (mean, 0.85 h) (10). This observation was consistent with the fact that clearance was reduced while the volume of distribution was increased, which would result in an increased elimination halflife (elimination rate constant k = CL/V) (15). This indicated that the retention time of esomeprazole in critically ill patients is prolonged.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The mean t 1/2 of esomeprazole in this study (3.29 h) was much higher than that reported in healthy volunteers (mean, 0.85 h) (10). This observation was consistent with the fact that clearance was reduced while the volume of distribution was increased, which would result in an increased elimination halflife (elimination rate constant k = CL/V) (15). This indicated that the retention time of esomeprazole in critically ill patients is prolonged.…”
Section: Discussionsupporting
confidence: 87%
“…Blood samples were collected according to the scheduled time and the concentration of esomeprazole in plasma and were determined by UPLC-MS/MS according to a previous method [15]. The chromatographic column was the ACQUITY UPLC BEH C18 column (2.1× 50 mm, 1.7 um).…”
Section: Sample Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…While the inhibition of CYP3A4 by these compounds (except SA1) can result in a decrease in the metabolism of some toxins, including the parent drug, that leads to its accumulation and an increased risk of toxicity. Moreover, this action can affect the metabolism of other drugs taken simultaneously with these compounds, leading to drug-drug interaction [54]. Additionally, the produced fused coumarin compounds have a very high plasma protein binding capacity which can result in a decrease in the volume of distribution and a reduction in the half-life of these compounds [55].…”
Section: Theoretical Pharmacokinetic Parametersmentioning
confidence: 99%
“…Secondly, the ability of the synthesized coumarins to inhibit CYP2C9 may indicate that these coumarins have an antiinflammatory potential since this enzyme metabolizes the arachidonic acid to the inflammatory signaling molecule named eicosatrienoic acid epoxide [20]. Thirdly, the synthesized coumarins have a high capacity for binding with plasma proteins resulting in the dropping of the distribution volume and consequently shorting their half-lives [21]. Finally, the poor inclusion through blood-brain barrier may indicate that these coumarins are free from the neurological side effects and this issue is highly important in the term of toxicity [22].…”
Section: Theoretical Pharmacokinetic Evaluationmentioning
confidence: 99%